Deficit Irrigation Effects on Cabbage (Brassicaceae Oleracea var. capitata L. Grandslam F1) Yield in Unheated Greenhouse Condition - Hakan Büyükcangaz (Turkish Journal of Agriculture: Food Science and Technology, 2018)
The aim of this study was to determine the effect of deficit irrigation on yield for cabbage grown under unheated greenhouse condition. The research was carried out at the Agricultural Research Station of Yenişehir High School of Uludağ University in Bursa, Turkey, in 2008. In the study, water was applied to cabbage as 1.00, 0.75, 0.50, 0.25 and 0.00% (as control) of evaporation from a Class A Pan corresponding to 2 day irrigation frequency. Irrigation water applied ranged from 70 to 520 mm and water consumption ranged from 90 to 548 mm. The effect of irrigation water level on the yield, head height, head diameter, head weight and dry matter were found to be significant. The highest yield was 72.8 t ha-1. Crop yield response factor for cabbage (ky) was found as 1.036. The highest values of water use efficiency (WUE) and irrigation water use efficiency (IWUE) for 2008 year of K2cp treatment was calculated to be 0.143 kg m-3 and 0.137 kg m-3, respectively. K2cp application (75%) can be recommended as the most effective irrigation level for the cabbage to which drip irrigation is applied under scarce and unheated greenhouse conditions.